Factors Influencing the Purchase Decision of Perfumes with Habit as a Mediating Variable:An Empirical Study in Malaysia - Azeema, Noor; Jayaraman, K.; Kiumarsi, S. (Indian Journal of Marketing, 2016)
The majority of the Malaysian consumers prefer to use perfumes since the average daily sunshine duration in Malaysia ranges from 4-8 hours per day, irrespective of the months of the year. The decomposed stimulus-organism-response (S-O-R) model was applied in this study with the purchase characteristics of perfumes form the stimulus (S), habit as the organism (O), and the purchase decision as the response (R). About 164 respondents in Peninsular Malaysia were included in this primary questionnaire survey, of which 81 (49.4%) favored branded perfumes and 83 (50.6%) preferred non-branded perfumes. The attractive packaging and seasonal variations in fragrance and flavor of the perfumes were highly prioritized by the respondents. The significant findings of the study revealed that habit of using perfume mediates the relationship between message framing and perceived quality on the purchase decision of perfumes. Surprisingly, there was no significant difference between branded and non-branded perfumes when the quality of the perfume was well maintained. Also, there was no significant difference in the usage of perfumes between men and women and between the races Malays and Chinese. The practical contribution of the present study involves in considering ’habit’ as the mediating variable which has direct and indirect implications on the purchase decision of perfumes. The established results of this article have many business implications for both manufacturers and consumers of perfumes.